DISCUSSING THE POSSIBILITIES AND CHALLENGES OF SCHOOL'S COOKS IN THE ACTIONS OF FOOD AND NUTRITION EDUCATION - Kelly dos Santos Gomes; Alexandre Brasil Carvalho da Fonseca (Universidade do Estado do Rio de Janeiro, 2018)
Objective: To discuss the role of school's cooks within the Brazilian National School Feeding Program, as well as its possibilities and challenges in the actions of Food and Nutrition Education. Methods: Qualitative research, using the techniques of participant observation and Choice Work Dialogue. The studied group consisted of 23 school's cooks from a city in the metropolitan region of Rio de Janeiro state. Results and Discussion: The educational potential of school's cooks is based on the relationships of affection they develop with students and on the qualifications they perform in order to develop new skills. However, the lack of time and of integration with the school staff are challenges for the fulfillment of the educational function of these professionals. Conclusion: The educational function of school's cooks is permeated by possibilities and challenges; hence, it is interesting to value its potential aspects for Food and Nutrition Education and to contribute to overcome its challenges. Thus, it will be possible to enjoy even more the educational potential of this program. DOI: 10.12957/demetra.2018.31340